Determinantes da mortalidade humana: evidência de dados brasileiros - Silva, Cristiano Coelho da (2021)
This paper studies determinants of human mortality between 2002 and 2019 in Brazil using more than 20 million data observations from the Ministry of Health as a probability of death for different bases of death (Diseases of the circulatory system, Neoplasms (tumors), External causes of morbidity and mortality and other causes) differ from biological (gender and race) and social characteristics (education level). The impact was studied separating as causes of deaths following the guidelines of the International Statistical Classification of Diseases and Health Related Problems (CID 10). We found that on average, the propensity of death for men and women does not differ when we do not take into account the underlying cause of death, in contrast, when we compare the propensity to die within of the same underlying cause of death, the impact of gender becomes an important component. We found that men are more likely to die from causes classified as preventable deaths, which are those linked to violence and behavioral characteristics. Women, in turn, have a higher proportion of deaths from diseases of the musculoskeletal system and connective tissue, diseases skin and subcutaneous tissue and endocrine, nutritional and metabolic diseases. When we compare self-declared non-white people in relation to self-declared white people, non-whites are more likely to die from preventable causes, linked to violence and behavior, just as men are in relation to women. We identified that the level of education also influence on the probability of death from different causes. We verify that people with higher education has a lower probability of death compared to a lower level of education, especially for diseases related to mental and behavioral disorders and external causes of morbidity and mortality. These results provide empirical support for stronger health systems of Brazil.